Community Cohesion A New Framework for Race and Diversity - Cantle, Ted. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
In this timely study, the author examines the historical approach to race and diversity and suggests that equality strategies have been a vital, but limited, means of addressing discrimination and community tensions. Community Cohesion, it argues, offers a new framework to break down the barriers between different communities and understand the more fundamental causes of racism and the 'fear of difference'. Concepts of multiculturalism, identity and citizenship are also reviewed and the developing practice of community cohesion is described.